2021
DOI: 10.3201/eid2703.201783
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma genitalium and Other Reproductive Tract Infections in Pregnant Women, Papua New Guinea, 2015–2017

Abstract: Much about the range of pathogens, frequency of coinfection, and clinical effects of reproductive tract infections (RTIs) among pregnant women remains unknown. We report on RTIs ( Mycoplasma genitalium , Chlamydia trachomatis , Neisseria gonorrhoeae , Trichomonas vaginalis , Treponema pallidum subspecies pallidum , bacterial vaginosis, and vulvovaginal candidiasis) and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Rates of low-birth weight babies (< 2500 g) in East New Britain are slightly higher than the national average (7.3% vs 6.9%) [ 34 ]. Other local determinants of poorer newborn health outcomes include high rates of unintended pregnancy, low levels of family planning [ 35 ] and a high burden of reproductive tract infections [ 36 ]. In 2018, the year prior to commencement of this study, an early essential newborn care workshop was held in East New Britain with over 20 participants attending from various health facilities in East New Britain Province.…”
Section: Methodsmentioning
confidence: 99%
“…Rates of low-birth weight babies (< 2500 g) in East New Britain are slightly higher than the national average (7.3% vs 6.9%) [ 34 ]. Other local determinants of poorer newborn health outcomes include high rates of unintended pregnancy, low levels of family planning [ 35 ] and a high burden of reproductive tract infections [ 36 ]. In 2018, the year prior to commencement of this study, an early essential newborn care workshop was held in East New Britain with over 20 participants attending from various health facilities in East New Britain Province.…”
Section: Methodsmentioning
confidence: 99%
“…Approximately, 60% of births occur in health facilities, above the PNG national average of 36% [22]. The province is similar to much of PNG in terms of disease profile and geography, including high rates of unintended pregnancy, low rates of contraception use [23], high burden of reproductive infections [24], and gaps in childhood immunization coverage [25]. East New Britain's mountainous interior renders some communities accessible only by walking tracks, and coastal villages generally only accessible by water.…”
Section: Study Design and Settingmentioning
confidence: 99%
“…The prevalence of Mycoplasma genitalium (MG) among pregnant women is estimated to be about 1% in high-income countries, but as high as 12% in South Africa and Papua New Guinea 7 8. A systematic review was conducted to examine the associations between MG infections identified during pregnancy with adverse outcomes, including spontaneous abortion, preterm birth, premature rupture of membranes, low birth weight and perinatal death 9.…”
Section: Published In Sexually Transmitted Infections the Editor’s Ch...mentioning
confidence: 99%